Phytochemical Composition and Biological Activities of Arctium minus (Hill) Bernh.: A Potential Candidate as Antioxidant, Enzyme Inhibitor, and Cytotoxic Agent - Selen İlgün; Gökçe Şeker Karatoprak; Derya Çiçek Polat; Esra Köngül Şafak; Gülsüm Yıldız; Esra Küpeli Akkol; Eduardo Sobarzo-Sánchez (MDPI AG, 2022)
Arctium minus (Hill) Bernh. (Asteraceae), which has a wide distribution area in Turkey, is a medicinally important plant. Eighty percent methanol extracts of the leaf, flower head, and root parts of A. minus were prepared and their sub-fractions were obtained. Spectrophotometric and chromatographic (high-performance liquid chromatography) techniques were used to assess the phytochemical composition. The extracts were evaluated for antioxidant activity by diphenyl-2-picrylhydrazil radical (DPPH●), 2,2'-Azino-bis 3-ethylbenzothiazoline-6-sulfonic acid (ABTS●+) radical scavenging, and β-carotene linoleic acid bleaching assays. Furthermore, the extracts were subjected to α-amylase, α-glucosidase, lipoxygenase, and tyrosinase enzyme inhibition tests. The cytotoxic effects of extracts were investigated on MCF-7 and MDA-MB-231 breast cancer cell lines. The richest extract in terms of phenolic compounds was identified as the ethyl acetate sub-fraction of the root extract (364.37 ± 7.18 mgGAE/gextact). Furthermore, chlorogenic acid (8.855 ± 0.175%) and rutin (8.359 ± 0.125%) were identified as the primary components in the leaves' ethyl acetate sub-fraction. According to all methods, it was observed that the extracts with the highest antioxidant activity were the flower and leaf ethyl acetate fractions. Additionally, ABTS radical scavenging activity of roots' ethyl acetate sub-fraction (2.51 ± 0.09 mmol/L Trolox) was observed to be as effective as that of flower and leaf ethyl acetate fractions at 0.5 mg/mL. In the β-carotene linoleic acid bleaching assay, leaves' methanol extract showed the highest antioxidant capacity (1422.47 ± 76.85) at 30 min. The enzyme activity data showed that α-glucosidase enzyme inhibition of leaf dichloromethane extract was moderately high, with an 87.12 ± 8.06% inhibition value. Lipoxygenase enzyme inhibition was weakly detected in all sub-fractions. Leaf methanol extract, leaf butanol, and root ethyl acetate sub-fractions showed 99% tyrosinase enzyme inhibition. Finally, it was discovered that dichloromethane extracts of leaves, roots, and flowers had high cytotoxic effects on the MDA-MB-231 cell line, with IC50 values of 21.39 ± 2.43, 13.41 ± 2.37, and 10.80 ± 1.26 µg/mL, respectively. The evaluation of the plant extracts in terms of several bioactivity tests revealed extremely positive outcomes. The data of this study, in which all parts of the plant were investigated in detail for the first time, offer promising results for future research.